Healthy Living: Food Can Affect Your Medicines - Paulina Wittkowsky; Linda B. Bobrof (EDIS)
Do the foods you eat affect the way your medicines work? It’s very possible. Certain foods can affect the way prescription and over-the-counter medicines work by delaying, decreasing, or enhancing how much of the drug is absorbed by the body. This can cause unwanted and harmful side effects. Follow the information in this revised 2-page fact sheet to reduce your risk of common food and drug interactions. Written by Paulina Wittkowsky and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, May 2014.